(3cJGH aj GdfMhs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s ((3jGbhJ GdeSJYUi s)
(3ChdgG (B:s
(3bGd GdGeGe GdeYQha HGHf GdMGLH QMeg Gddg GdcdeI daX hVY eYfi eaQO hgj GSe haYd hMQa s
(3BNQgG (B:s
(3hGdeNaag JMPa ddSGcf hai Gdhba ajQO eG MPa hGdeaJhM eG bHdgG JbdH CdakG JeJ GdCbSGe GdKdGKI HMeO Gddg JYGdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1370s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs